Analisis Yuridis Terhadap Batas Usia Minimal Perkawinan Berdasarkan Undang-Undang Nomor 16 Pasal 7 Tahun 2019: Studi kasus Pengadilan Agama Sungguminasa - Huda, Nurul; Idrus, Achmad Musyahid; Sabir, Muhammad (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Child marriage is always motivated by various things or commonly referred to as factors, this factor is what encourages a child to marry or want to marry under the age of the provisions that already exist in legislation Number 16 of 2019 concerning marriage, namely in article 7 paragraph 1 which states that those who are allowed to marry when they reach the age of 19 years. Low marriage education is one of the factors for child marriage, which increases every year. In terms of child marriage, one of the factors that influence the occurrence of child marriage is not in accordance with the provisions of Law Number 16 of 2019 concerning marriage, namely the age of 19 years namely due to a lack of knowledge about child marriage, such as a lack of understanding of the impacts that will result from a marriage, both good and bad impacts. This research uses a field methodology (Field Research), namely research that has been carried out by being directly on the object, especially in an effort to collect data and information. And the type of research used is qualitative research. The implication of this research is that underage marriages that occur in Sungguminasa Regency, they are forced to marry due to several factors such as pregnancy outside of marriage, promiscuity, economy, education, custom, arranged marriage and their own desires this is due to lack of supervision and lack of interest in education so that quarrels and violence occur.